Clathrin light chain‐conjugated drug delivery for cancer. Issue 1 (28th November 2022) - Jung, Sungwook; Jiang, Liwei; Zhao, Jing; Shultz, Leonard D.; Greiner, Dale L.; Bae, Munhyung; Li, Xiaofei; Ordikhani, Farideh; Kuai, Rui; Joseph, John; Kasinath, Vivek; Elmaleh, David R.; et al.
Abstract: Targeted drug delivery systems hold the remarkable potential to improve the therapeutic index of anticancer medications markedly. Here, we report a targeted delivery platform for cancer treatment using clathrin light chain (CLC)‐conjugated drugs. We conjugated CLC to paclitaxel (PTX) through a glutaric anhydride at high efficiency. Labeled CLCs localized to 4T1 tumors implanted in mice, and conjugation of PTX to CLC enhanced its delivery to these tumors. Treatment of three different mouse models of cancer—melanoma, breast cancer, and lung cancer—with CLC‐PTX resulted in significant growth inhibition of both the primary tumor and metastatic lesions, as compared to treatment with free PTX. CLC‐PTX treatment caused a marked increase in apoptosis of tumor cells and reduction of tumor angiogenesis. Our data suggested HSP70 as a binding partner for CLC. Our study demonstrates that CLC‐based drug‐conjugates constitute a novel drug delivery platform that can augment the effects of chemotherapeutics in treating a variety of cancers. Moreover, conjugation of therapeutics with CLC may be used as means by which drugs are delivered specifically to primary tumors and metastatic lesions, thereby prolonging the survival of cancer patients.